Implementasi E-Government Melalui Sistem Persuratan Elektronik Pada Kementerian Sekretariat Negara Republik Indonesia - Widodo, Widodo; Santodo, Seno; Badar, Refly (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study is the result of research conducted at the General Bureau of the General Secretariat of the Ministry of State Secretariat regarding the implementation of electronic mail systems in support of Electronic Government. This research was conducted using a descriptive-qualitative method. Through the E-Government theory approach quoted from Indrajit (2016), the researcher examines implementation based on three components, namely: (1) Support, in the form of policies that are the legal basis for the development of SPDE Open, namely PP No. 95 of 2018 concerning Systems Electronic Based Government; (2) Capability, broadly speaking, the ability is demonstrated by granting authority to the Bureau of Information, Data and Technology work units to develop systems, provision of tools or equipment channelled through the State Budget and development of the human resources themselves; and (3) Value which are the impact of implementation, this application can simplify mailing procedures, make employee mobility more efficient and effective and reinforce the directions given so that it can be said that the implementation of SPDE Open has reached the transformation phase, where a system has experienced further development so that services increase in an integrated manner. While the obstacles found in this research are of a technical nature where the display of the application website is not yet user-friendly and the unpreparedness of employees in accepting SPDE Open as part of work priorities, for this reason, further research is needed to find solutions to existing problems.